Pengaruh Prenatal Yoga terhadap Depresi, Kecemasan dan Stres pada Ibu Hamil - Susanti, Indhun Dyah (Indonesian Journal Publisher, 2025)
Background: Pregnancy is often accompanied by physical and psychological changes that can increase the risk of depression, anxiety, and stress, which negatively impact the health of the mother and fetus. Prenatal yoga is considered a safe and effective non-pharmacological intervention to help reduce depression, anxiety, and stress in pregnant women. Purpose This study aims to analyze the effect of prenatal yoga on depression, anxiety, and stress in pregnant women. Methods: This study used a quasi-experimental pretest–posttest control group design. The sample consisted of 60 pregnant women who were divided evenly into the intervention group (n=30) and the control group (n=30) with a purposive sampling technique. Data were collected using the DASS-21 questionnaire. Data analysis was performed using a paired t-test to see changes within the group and an independent t-test to compare differences between groups with a significance level of 95%. Results The results showed a significant decrease in depression, anxiety, and stress scores after prenatal yoga intervention in the intervention group. The control group did not show significant changes in the three variables. Intergroup analysis showed a significant difference (p < 0.001). Conclusion: Prenatal yoga has been shown to be effective in reducing depression, anxiety, and stress in pregnant women, and can therefore be recommended as a safe, non-pharmacological intervention in antenatal care. This program is recommended for integration into healthcare facilities as a promotive and preventive measure to improve the mental health of pregnant women and support optimal fetal development.